2018
DOI: 10.1007/s10695-018-0552-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial replacement of fish meal by yeast hydrolysate on antioxidant capability, intestinal morphology, and inflammation-related gene expression of juvenile Jian carp (Cyprinus carpio var. Jian)

Abstract: This study aimed to evaluate the effects of fish meal (FM) replacement by yeast hydrolysate (YH) on liver antioxidant capability, intestinal morphology, and inflammation-related genes of juvenile Jian carp (Cyprinus carpio var. Jian). A total of 600 fish (average initial weight 19.44 ± 0.06 g) were randomly selected and divided into five groups. Five isonitrogenous and isocaloric diets replacing FM by YH 0% (YH0), 1% (YH1), 3% (YH3), 5% (YH5), and 7% (YH7) were formulated. Each diet was tested in four replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…Similar with our results, Fu et al [ 26 ] presented that supplementing YH increased jejunal VH and VH/CD as well as gut development-related genes expression to maintain intestinal integrity in weaned piglets. A previous study showed that dietary Saccharomyces cerevisiae hydrolysate increased the villus length and muscle thickness in the foregut and midgut as well as intestinal microvillus length and density in aquatic animals, thus increasing the intestinal absorptive surface area and improving nutrient capture [ 6 ], which might help to improve feed efficiency. Besides, other yeast-derived additives including live yeast and yeast culture also showed positive effects on intestinal morphology [ 13 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar with our results, Fu et al [ 26 ] presented that supplementing YH increased jejunal VH and VH/CD as well as gut development-related genes expression to maintain intestinal integrity in weaned piglets. A previous study showed that dietary Saccharomyces cerevisiae hydrolysate increased the villus length and muscle thickness in the foregut and midgut as well as intestinal microvillus length and density in aquatic animals, thus increasing the intestinal absorptive surface area and improving nutrient capture [ 6 ], which might help to improve feed efficiency. Besides, other yeast-derived additives including live yeast and yeast culture also showed positive effects on intestinal morphology [ 13 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin 10, secreted by activated macrophages, is a key cytokine to restrain the excessive production of pro-inflammatory cytokines and maintain immune balance of the body [ 13 ]. Conversely, TNF-α is a pro-inflammatory cytokine mainly produced by macrophages and monocytes, which level increases in many pathological conditions [ 5 , 6 ]. An article reported that lower serum immunoglobulins A and E levels and higher intestinal TNF-α level were observed in IL-10 gene knockout mice compared with the mice without knockout [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Replacing fish meal with high concentrations of plant proteins can cause inflammatory reactions in the intestinal tract (Urán et al, 2008;Yuan et al, 2019). Most research on the inflammatory response focuses on the intestines rather than the liver.…”
Section: Discussionmentioning
confidence: 99%